Is the Nature of Communication Relevant to the Supportiveness of Women's Relationships With Probation and Parole Agents?. (May 2018) - Morash, Merry; Kashy, Deborah A.; Smith, Sandi W.; Cobbina, Jennifer E.
This article reports on a study of the connection of probation and parole agents' communication with relationship supportiveness as perceived by both women offenders and agents. For a sample of offenders and their agents, multilevel modeling was used to control for nonindependence of data for women assigned to the same agent. Consistent with communication theory, a conversational approach was positively related to measures of a supportive relationship, and an authoritarian/ conformity pattern of communication was negatively related to a supportive relationship. For low-risk offenders, attention to client-identified problems was positively related to more supportive relationships. For women with high risk for reoffending, the agents viewed themselves as less supportive if they addressed a high proportion of offender-identified needs. Findings suggest the efficacy of training to promote agents' conversational communication and attention to offender-identified problems. Findings also suggest the need to more fully explore agents' experience in working with very high-risk offenders.